Redes de infra-estrutura urbana : gestão de programas e projetos na cidade de Passo Fundo de 2005 a 2007 - Kalil, Ramadan (2008)
The objective of this investigation is to deal with the management of programs and projects of urban infrastructure networks, approaching articulation between the internal municipal departments and the external agencies responsable for the infraestructure in the City of Passo Fundo, in the Rio Grande do Sul State. Despite the town has stablished sanitation (1910) and master plans (1953, 1984 and 2006), which defined the road system and the general guidelines of infrastructure planning, there is difficulty of implementation as well as management of urban space and its infrastructure network. Add to this the skill diversity of several public and private agents related to it. The general objective of this research was to identify and assess the management and planning procedures of the urban infrastructure networks in the town of Passo Fundo in the period between 2005 and 2007, aiming subsidize the public and private agents responsible for the implementation, integration and maintenance of urban networks, contributing to the improvement of urban services quality and providing the sustainable development of the city. The management approachs of programs and projects of the following networks has been assessed: urban road network; urban drainage network; potable water supply network; sanitary sewage network; electrical energy network (home supply and public lighting); green network: (urban afforestation, parks and waste collecting). Based on the literature review about the theme, the networks have been studied as to their operation and coverage, programs and projects, management and articulation between public sectors and dealership companies. The study was based on the analisys of collected data documentation from municipal departments and the external agencies. Interviews with technicians and leaders of these sectors have been also accomplished. The results of the works are presented in such a descriptive way, texts, charts, tables and images, approaching the programs management processes and projects of the urban infrastructure networks in development in Passo Fundo. It also presents the assessment and discussion of the results in comparison with the literature review. It realized that, in the most networks, the strategic planning, information management, public participation, methods for continuous improvement and demand and supply priority present themselves precarious management. From these indicators, guidelines for management optimization of the urban infrastructure networks in Passo Fundo are proposed. Finally, conclusions and recommendations are presented, emphasizing that the quality and sustainability of the urban infrastructure networks and its services, depend on the integration between the departmens and the companies responsible for planning and management and the community